THE IMPACT OF THE MEDIA TOURNAMENT ON THE STUDENTS’ INFORMATION AND MEDIA LITERACY LEVEL - YACHMENYK, Maryna (Physical and Mathematical Education, 2024)
Formulation of the problem. In the context of military aggression and hybrid warfare, it is essential to form young people’s critical thinking to combat disinformation. Therefore, info-media literacy is gaining relevance as an important personal characteristic of every member of Ukrainian society. The analysis of Ukrainian scientific sources has shown that more attention should be paid to the formation of info-media literacy of young people in extracurricular activities, one of the modern forms of which is a media tournament. Therefore, the study aims to substantiate the media tournament’s positive impact on the students’ information-media literacy level. Materials and methods. To confirm the effectiveness of the Media Tournament, we used a survey. The survey results were processed according to the criterion of signs (non-parameter criterion). The total number of participants is 50. Statistical analysis was carried out on 15 answer options. Results. We described the stages of the tournament (writing a motivation letter; training BarCamp "Online Tools," workshop "Media Literacy Tools in the Study of Literary Works," the workshop "Formation of skills for evaluating and interpreting media information," training "Language Media Workshop," presentation of own media developments). The statistical analysis is confirmed that the media tournament positively affects young people’s information and media literacy, characterized by media literacy, critical thinking, social tolerance, fact-checking, information literacy, digital security, visual literacy, and creativity. Conclusions. Discussion teaching methods and auxiliary virtual tools develop the student’s ability to analyze media texts formed and work with the content of various formats, contributing to developing students’ critical thinking at the same time. Also, we constellated the lack of a purposeful policy for creating information and media literacy for school students. The tournament proved effective as an educational activity and can, therefore, be used to develop media literacy among young people.